2020
DOI: 10.1111/jcmm.15952
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Aster tataricus extract on NLRP3‐mediated pyroptosis of bladder urothelial cells

Abstract: Aster tataricus L.f. is a traditional Eastern Asian herbal medicine used for the relief of uroschesis‐related illnesses and has been demonstrated clinically to exert satisfied effects. However, the mechanism of its therapeutic action remains unclear. The present study aimed to evaluate the protective mechanism of Aster tataricus extract (ATE) on CYP or LPS + ATP‐induced interstitial cystitis (IC), we successfully constructed the induced IC Sprague‐Dawley (SD) rat model and IC human urothelium cell (SV‐HUC‐1) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In IC/BPS, the use of several medicinal plants has been evaluated in experimental models. For example, Aster tataricus extract and its main active component Shionone were shown to reduce bladder inflammation in IC rats and decrease pyroptosis in the SV-HUC1 urothelial cell line, by inhibiting the NLRP3–GSDMD pathway [ 95 , 96 ], while intravesical treatment with Bletilla striata extract solution was shown to attenuate visceral hypersensitivity and bladder overactivity in zymosan-induced-IC in SD rats [ 97 ]. Treatment with Olea europaea or Juniperus procera leaf extracts in SD rats with stress (water deprivation)-induced IC reduced bladder mast cell infiltration and levels of stress hormones [ 98 ], and Houttuynia cordata extract inhibited mast cell proliferation and activation, decreased the levels of proinflammatory cytokines IL6, IL8, and TNFα, and reduced inter-contraction intervals in SD rats with CYP-induced IC [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…In IC/BPS, the use of several medicinal plants has been evaluated in experimental models. For example, Aster tataricus extract and its main active component Shionone were shown to reduce bladder inflammation in IC rats and decrease pyroptosis in the SV-HUC1 urothelial cell line, by inhibiting the NLRP3–GSDMD pathway [ 95 , 96 ], while intravesical treatment with Bletilla striata extract solution was shown to attenuate visceral hypersensitivity and bladder overactivity in zymosan-induced-IC in SD rats [ 97 ]. Treatment with Olea europaea or Juniperus procera leaf extracts in SD rats with stress (water deprivation)-induced IC reduced bladder mast cell infiltration and levels of stress hormones [ 98 ], and Houttuynia cordata extract inhibited mast cell proliferation and activation, decreased the levels of proinflammatory cytokines IL6, IL8, and TNFα, and reduced inter-contraction intervals in SD rats with CYP-induced IC [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…A. tataricus has been used as a traditional medicinal herb in China for more than 2,000 years due to its medicinal properties, such as anti-oxidation, anti-inflammatory, and anti-cancer, for humans (Du et al 2017 ; Li et al 2021b ; Su et al 2019 ; Wang et al 2020 ). Li et al reported that the anti-lung cancer function of A. tataricus is closely related to flavonoids such as quercetin, kaempferol, isorhamnetin, and luteolin (Li et al 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…(2R,2′R)-7-O-methyl–2,3,2′′,3′′–tetrahydrorobustaflavone, a new flavonoid isolated from A. tataricus , can significantly inhibit A594 cancer cells proliferation (Chen et al 2022 ). As the largest group of secondary metabolites in plants, flavonoids not only contribute to diverse human health benefits, but also provide plants with a variety of biological functions, such as diseases treatment for humans and stress resistance for plants (Ng et al 2003 ; Treutter 2005 ; Wang et al 2020 ; Wen et al 2021 ). Flavonols may facilitate maize ( Zea mays ) seedling drought tolerance by scavenging H 2 O 2 and stomatal closure (Li et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an in vivo study [ 3 ] showed that the Fr-50 fraction (40, 80 mg/kg) of a 70% ethanolic extract from RA root significantly enhanced tracheal phenol red secretion, prolonged latency, reduced cough frequency, and suppressed mouse ear edema. Wang et al [ 42 ] found that extract of RA could reduce the edema and hemorrhage in the bladder of rats with interstitial cystitis, and extract of RA significantly reduced other pyrolysis of in vivo and in vitro death-related proteins. These results indicated that the different extracts of RA attenuated the inflammatory reaction by inhibiting various inflammatory mediators ( Figure 8 ).…”
Section: Pharmacological Activitymentioning
confidence: 99%